Distribution of bird nest and stag horn fern in UiTM Forest Reserve, Jengka, Pahang / Mohd Zamri Ibrahim - Ibrahim, Mohd Zamri (2001)
This project comprehend all the observation and recognition the distribution of bird's nest and stag's horn fern in UiTM Forest Reserve of Pahang. The main objective of the study is to know the distribution of bird's nest and stag's horn fern that can be found in UiTM Forest Reserve. Beside that the characteristic of can be recognized. From this, one best result can be make. Beside that, it can be known for the commercial plant especially for landscaping plant.